Simplified and robust one‐step radiosynthesis of [18F]DCFPyL via direct radiofluorination and cartridge‐based purification. (23rd May 2018) - Dornan, Mark H.; Simard, José‐Mathieu; Leblond, Antoine; Juneau, Daniel; Delouya, Guila; Saad, Fred; Ménard, Cynthia; DaSilva, Jean N.
Abstract : [ 18 F]DCFPyL is a clinical‐stage PET radiotracer used to image prostate cancer. This report details the efficient production of [ 18 F]DCFPyL using single‐step direct radiofluorination, without the use of carboxylic acid‐protecting groups. Radiolabeling reaction optimization studies revealed an inverse correlation between the amount of precursor used and the radiochemical yield. This simplified approach enabled automated preparation of [ 18 F]DCFPyL within 28 minutes using HPLC purification (26% ± 6%, at EOS, n = 4), which was then scaled up for large‐batch production to generate 1.46 ± 0.23 Ci of [ 18 F]DCFPyL at EOS (n = 7) in high molar activity (37 933 ± 4158 mCi/μmol, 1403 ± 153 GBq/μmol, at EOS, n = 7). Further, this work enabled the development of [ 18 F]DCFPyL production in 21 minutes using an easy cartridge‐based purification (25% ± 9% radiochemical yield, at EOS, n = 3). Abstract : One‐step radiosynthesis of [ 18 F]DCFPyL via direct radiofluorination and cartridge‐based purification.